Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0150954
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of Nickel Nanoparticles-Induced Toxicity by Epigallocatechin-3-Gallate in JB6 Cells May Be through Down-Regulation of the MAPK Signaling Pathways

Abstract: With the rapid development in nanotechnology, nickel nanoparticles (Ni NPs) have emerged in the application of nanomedicine in recent years. However, the potential adverse health effects of Ni NPs are unclear. In this study, we examined the inhibition effects of epigallocatechin-3-gallate (EGCG) on the toxicity induced by Ni NPs in mouse epidermal cell line (JB6 cell). MTT assay showed that Ni NPs induced cytotoxicity in a dose-dependent manner while EGCG exerted a certain inhibition on the toxicity. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 37 publications
(35 reference statements)
0
13
0
3
Order By: Relevance
“…The methyl thiazolyl tetrazolium (MTT) (Sigma, St. Louis, MO) colorimetric assay was used to screen for cell proliferation as previously described (Sun, He, et al, ). To further investigate cell proliferation, a cell cycle staining Kit was used (Liankebio, Hangzhou, China) according to the manufacturer's instructions (Gu et al, ). Cell apoptosis analysis was carried out using the Annexin V‐FITC/PI apoptosis kit (Lager et al, ), Annexin‐V‐positive and PI‐negative cells were defined as early apoptotic cells, and the late apoptotic cells were Annexin‐V and PI positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…The methyl thiazolyl tetrazolium (MTT) (Sigma, St. Louis, MO) colorimetric assay was used to screen for cell proliferation as previously described (Sun, He, et al, ). To further investigate cell proliferation, a cell cycle staining Kit was used (Liankebio, Hangzhou, China) according to the manufacturer's instructions (Gu et al, ). Cell apoptosis analysis was carried out using the Annexin V‐FITC/PI apoptosis kit (Lager et al, ), Annexin‐V‐positive and PI‐negative cells were defined as early apoptotic cells, and the late apoptotic cells were Annexin‐V and PI positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were harvested 48 h later and washed three times by cold PBS, and then fixed in 70% ethanol in PBS at -20°C overnight. And then the cells were incubated with 0.5 ml of propidium iodide (PI) staining buffer, which contains 200 μg/ml RNase A and 50 μg/ml PI, at 37°C in the dark for 30 min [ 36 ]. Analyses were performed on BD LSR flow cytometer (BD Biosciences, San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Normally, ROS generation and quenching are in a dynamic balance state due to the intracellular antioxidant system. Certain harmful extracellular factors may break this balance, resulting in excessive ROS generation beyond the cell scavenging ability to then induce organelle damage, abnormal expression of proteins or eventually cell death ( 33 35 ). Studies have demonstrated that most heavy metal ions cause excessive intracellular ROS generation ( 12 , 22 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%